UNCONTROLLED TYPE 1 DIABETES MELLITUS WITH TUBERCULOMA IN INFERIOR LOBE LEFT LUNG AND BILATERAL HYDRONEPHROSIS IN CHILD - Wardhana, Anggia Rarasati; Sukartini, Sukartini; Muhyi, Annisa (Jurnal Ilmu Kesehatan dan Kesehatan, 2019)
Diabetes Mellitus (DM) is an important risk factor for the development of active tuberculosis (TB). It is chronic and will weaken the immune system causing the patient have increased risk of tuberculosis by three-fold.We present a case of 13-year-old girl with chest pain and cough. She has a previous history of type 1 DM. Laboratory findings showed hyperglycemic state. Thoracic CT showed tuberculoma of inferoposterior lobe left lung, while abdominal CT showed bilateral hydronephrosis. He was then administered TB treatment of 2HRZE/10RH, corticosteroid, and insulin regiments with strict monitoring of blood glucoses. Clinical symptoms and blood glucose level were significantly improved after treatment.